Enhancing the Effectiveness of Public Spending in Finland - Hemmings, Philip (OECD Publishing, 2003)
Finland is committed to high quality and extensive public services and a high level of income redistribution. The heavy tax burden these commitments require is becoming increasingly difficult to sustain due to tax competition and the need to harmonise certain taxes with other EU countries. These pressures on taxation combined with the fiscal effects of rapid ageing imply a need for continued restraint of aggregate expenditure and a need for further efficiency gains in the provision of public services. This paper, one of a series of OECD reviews on public expenditure, looks at how Finland is coping with this challenge. It concludes that the fundamental framework guiding public expenditure in Finland is sound. And, in many areas of public activity the country compares very favourably internationally. However, recent slippage in fiscal discipline needs to be addressed. Also it will be important to monitor, and if necessary follow up on, reforms of pensions and early retirement ...
Keywords: Economics; Finland